(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2018)
Background: In India, Tuberculosis (TB) is endemic and Human immunodefi ciency virus (HIV) infection is epidemic in few states. The risk of developing TB in people living with HIV (PLHIV) is about 19 (27-22) times greater than those without it. TB is major cause of death in HIV-TB co-infected patients. Globally 0.4 million deaths occur annually due to HIV-TB disease. Material & Methods:The present observational study was conducted at Darbhanga Medical College and Hospital ART (Antiretroviral therapy) center during period from January to June 2017. Data of HIV-TB co-infected patients was collected from HIV-TB register and entered into Microsoft Excel sheet for analysis using Statistical Package for the Social Sciences. Results:Young persons mostly from the labouring class working in other states were most affected. Pulmonary tuberculosis (sputum smear positive) was most common co-infection. Baseline CD4 cell count at the time of presentation was observed to be low (less than 200 cells/μL) in 46.64℅ HIV-TB co-infected patients. Conclusion: Rural young people working as migrant labourer need focus of health interventions. They should be educated and screened for HIV and TB. Baseline CD4 cell count should be done in all PLHIV cases to assess their immune status. SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, Vol. 14, No. 2, 2017, Page: 12-17